1983
DOI: 10.1084/jem.158.6.1948
|View full text |Cite
|
Sign up to set email alerts
|

Role of variable region gene expression and environmental selection in determining the antiphosphorylcholine B cell repertoire.

Abstract: To evaluate the role of environmental selective processes, as opposed to variable region gene expression, in the determination of B cell repertoire expression, we have assessed the phosphorylcholine (PC)-specific repertoire of precursor cells that remain in bone marrow cell populations after the removal of surface immunoglobulin (sIg)-bearing cells. Such cells are assumed to represent a stage in B cell maturation before the expression of sIg, and thus at a time when they have not as yet interfaced with environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
5
24
1
Order By: Relevance
“…It is fortuitous, then, that the correction factor for efficiency of the assay and our theoretical value of FIT happen to be close. Before discussing the uncorrected data, how are they explained by Klinman & Stone (1983)?…”
Section: // Testing Protecton Theorymentioning
confidence: 99%
“…It is fortuitous, then, that the correction factor for efficiency of the assay and our theoretical value of FIT happen to be close. Before discussing the uncorrected data, how are they explained by Klinman & Stone (1983)?…”
Section: // Testing Protecton Theorymentioning
confidence: 99%
“…This could reflect the basic organization of the resting repertoire. Klinman & Stone (1983) arrived at very similar conclusions from an analysis of the PC-specific repertoire of precursor cells in the bone marrow. The apparent diversity in the resting repertoire would be reduced to the extent that each individual clone was expanded.…”
Section: Discussionmentioning
confidence: 60%
“…In 1983 we also reported that, while newly developing B cells bearing various tested clonotypes were absent from the marrow of most large bones, bone marrows that did express a given clonotype often expressed more than one cell of that clonotype (Klinman & Stone 1983). Since bone marrow B cells do not appear to divide after L-chain rearrangement and slg expression, we proposed that the "clonal expansion" evidenced by this "jackpotting" of clonotypes in individual bone marrows was likely, at least in part, to be the product of considerable clonal expansion after Vi,-Di,-Jh rearrangement.…”
Section: B) H-chain Regulation Of Clonal Expansionmentioning
confidence: 89%
“…The "predetermined permutation" model was proposed, not as Cohn & Langman suggest, to account for the sequential acquisition of neonatal specificities, but rather to accomodate the high frequency of expression in BALB/c mice of anti-PC antibodies identical in VH and VL to the TEPC15 myeloma protein. In 1983 we demonstrated that "when T15 is expressed, it is not represented as inordinately large cell clones, but rather the expression of B cells bearing the T15 idiotype is an extraordinarily frequent event during repertoire generation" (Klinman & Stone 1983). (Note: Cohn & Langman quote us as concluding just the opposite).…”
Section: Rearrangement Without N Additionsmentioning
confidence: 99%